2020
DOI: 10.1088/1755-1315/492/1/012043
|View full text |Cite
|
Sign up to set email alerts
|

Brightness, elongation and thickness of edible film with caseinate sodium using a type of plasticizer

Abstract: The use of plasticizer could improve the flexibility, elasticity and friability of edible films. The characteristics of edible film made from caseinate sodium were influenced by the use of plasticizer types. The differences in material source and molecular weight of plasticizers type various result in the interaction of hydrogen bonds between water-protein-plasticizer molecules and further cause differences in the physical characteristics of edible films. The purpose of this study was to determine the effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…According to Maruddin et al, the addition of PEG, glycerol, and sorbitol plasticizers did not have a signi cant effect on the thickness of edible lms. Based on their research, the percentage of plasticizer and emulsi er used did not change the amount of composition and solids of the components [35].…”
Section: Film Thicknessmentioning
confidence: 98%
See 1 more Smart Citation
“…According to Maruddin et al, the addition of PEG, glycerol, and sorbitol plasticizers did not have a signi cant effect on the thickness of edible lms. Based on their research, the percentage of plasticizer and emulsi er used did not change the amount of composition and solids of the components [35].…”
Section: Film Thicknessmentioning
confidence: 98%
“…Thickness is the physical property of the lm that affects the penetration of volatile compounds, water vapor, and gases [35]. The thickness of the lm can vary depending on the components of the lm.…”
Section: Film Thicknessmentioning
confidence: 99%
“…The summarized information is presented in Table 1. Fruits, berries, vegetables, and chees, fish, meat and meat product [113,115,208,362,406,[434][435][436][437][438][439][440][441] Various meat products, poultry, fish, vegetables and fruits [113,139,406,[447][448][449][450][451][452][453][454][455] Edible films based on one biopolymer are often characterized high sensitivity to moisture and and poor barrier to water wapor due to its hydrophilicity nature, as well as brittleness and insufficient mechanical properties. These disadvantages could be solved by different modifications, cross-linking agents and plasticizers addition, and especially by creating composite films and blending.…”
Section: Ways Of Edible Films Improving Production and Application In Food Pachaging Based On Biopolymer Propertiesmentioning
confidence: 99%
“…Maruddin et al, 2020 [55] showed that plasticizers could improve the flexibility, elasticity and friability of edible films. The characteristics of edible ISSN: 2349-8889 Volume-8, Issue-5 (September 2021) https://doi.org/10.31033/ijrasb.8.5.22…”
Section: Iiiiv Thickness Of Edible Filmsmentioning
confidence: 99%